Graphic Indigeneity : Comics in the Americas and Australasia - Aldama, Frederick Luis, 1969- (Book collections on Project MUSE., 2020)
"Cultural works by and about Indigenous identities, histories, and experiences circulate far and wide. However, not all films, animation, television shows, and comic books lead to a nuanced understanding of Indigenous realities. Acclaimed comics scholar Frederick Luis Aldama shines light on how mainstream comics have clumsily distilled and reconstructed Indigenous identities and experiences. He and contributors emphasize how Indigenous comic artists are themselves clearing new visual-verbal narrative spaces for articulating more complex histories, cultures, experiences, and narratives of self. To that end, Aldama brings together scholarship that explores both the representation and misrepresentation of Indigenous subjects and experiences as well as research that analyzes and highlights the extraordinary work of Indigenous comic artists. Among others, the book examines Daniel Parada's Zotz, Puerto Rican comics Turey el Taíno and La Borinqueña, and Moonshot: The Indigenous Comics Collection. This volume's wide-armed embrace of comics by and about Indigenous peoples of the Americas and Australasia is a first step to understanding how the histories of colonial and imperial domination connect the violent wounds that still haunt across continents. Aldama and contributors resound this message: Indigeneity in comics is an important, powerful force within our visual-verbal narrative arts writ large."--